Laboratory diagnosis of COVID-19 cases from nasal and oropharyngeal swab specimens - Renatha, Nainggolan (Surgical Residency Program Syiah Kuala University, 2023)
Introduction: Indonesia first reported Covid-19 on March 2, 2020, which continued to increase and spread rapidly throughout Indonesia. WHO recommends molecular examinations for patients with suspected COVID-19 through molecular detection method or NAAT (Nucleic Acid Amplification Test), including Real Time-Polymerase Chain Reaction (RT-PCR) tests. This study aimed to describe the profile of RT-PCR test services on nasal and oropharyngeal swab specimens from patients treated at Dr. Pirngadi Hospital Medan and patients of primary health care (Puskesmas) or other hospitals referred for RT-PCR examination at the Laboratory of Dr. Pirngadi Hospital. Method: This was a retrospective, descriptive study using secondary data from medical records from August 2020 to July 2021. Using consecutive sampling, the study sample was all suspected and confirmed COVID-19 specimens collected at Dr. Pirngadi Hospital, Medan. All collected data were processed and analyzed using IBM SPSS version 20.0. Result: There were 7495 specimens of COVID-19 from Dr. Pirngadi Hospital from August 2020 to July 2021, of which 1264 (17%) were confirmed positive, and 6231 (83%) had negative results. Meanwhile, 12.274 specimens were obtained from primary health care or other hospitals, of which 2602 (2%) samples were confirmed positive, and 9672 (98%) had negative results. Based on sex, 884 men (44%) and 1108 women (56%) had confirmed COVID-19 cases. Conclusion: From August 2020 to July 2021, this study found 17% and 2% of confirmed COVID-19 cases at Dr. Pirngadi Hospital and primary health care or other hospitals, respectively. COVID-19-confirmed issues were more common in women.